Complications of Fracture Treatment by Traditional Bonesetters (Journal of Pakistan Orthopaedic Association, 2016)
Objective: To find out frequency of different complications in patients that has been managed by traditional bonesetters (TBS). Methods: This study was conducted from 1st October 2013 to 31st March 2014. Total 60 patients who presented at orthopedics out-patient clinic after treatment of traditional bone Setters were recruited for the study. Information about the patients' biodata, mechanism of injury, which advised them to contact TBS and complications after being managed by TBS were obtained. All the data thus obtained was put into and analyzed on SPSS version 17. Results: The mean age of 60 patients were 25.57 years with minimum 5 and maximum age was 65 years. Sixteen patients were females and 44 were male. Two (3.3%) of patients first attended Hospital and 58(96.7%) patients attended TBS. There were 51.7% mal-union, 31.7% non-union, 6.7% contracture and 6.7% gangrene and 3.3% developed infections. Conclusion: Mal-union/non-union, contractures and infections are the most common complications that patients are likely to suffer as a result of fracture treatment by TBS.Key Words: Traditional bonesetter (TBS), Treatment, Fracture, Complication.